1986
DOI: 10.1111/j.1432-1033.1986.tb09545.x
|View full text |Cite
|
Sign up to set email alerts
|

Cross-linking of elongation factor 2 to rat-liver ribosomal proteins by 2-iminothiolane

Abstract: Complexes containing rat liver 80s ribosomes treated with puromycin and high concentrations of KCl, elongation factor 2 (EF-2) from pig liver, and guanosine 5'-[/3,y-methylene]triphosphate were prepared. Neighboring proteins in the complexes were cross-linked with the bifunctional reagent 2-iminothiolane. Proteins were extracted and then separated into 22 fractions by chromatography on carboxymethylcellulose of which seven fractions were used for further analyses. Each protein fraction was subjected to diagona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

1990
1990
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(44 citation statements)
references
References 47 publications
2
41
0
1
Order By: Relevance
“…Moreover the ionic conditions are not identical in the two situations. It is clear that, in the cell, eEF-2 undergoes several other interactions with ribosomal proteins and rRNA [11,12]. The fact that we were unable to measure any interaction with eEF-2 when the P proteins were covalently linked to the sensor chip is possibly due to the fact that in the ribosome these proteins are flexible and at least partly mobile, as shown for their prokaryotic equivalents L7/L12 [13], whereas they were fixed on the sensor chip and could not move in our assay.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover the ionic conditions are not identical in the two situations. It is clear that, in the cell, eEF-2 undergoes several other interactions with ribosomal proteins and rRNA [11,12]. The fact that we were unable to measure any interaction with eEF-2 when the P proteins were covalently linked to the sensor chip is possibly due to the fact that in the ribosome these proteins are flexible and at least partly mobile, as shown for their prokaryotic equivalents L7/L12 [13], whereas they were fixed on the sensor chip and could not move in our assay.…”
Section: Discussionmentioning
confidence: 99%
“…Ribosomal Protein L10e Confers Sordarin Resistance-Identification of the large ribosomal subunit as the determinant of sordarin resistance, in addition to the biochemical and genetic associations of the stalk proteins with EF-G or eEF2 (11,13,(15)(16)(17)(18)(19), focused our efforts on the ribosomal stalk proteins. Because both fusidic acid and sordarin stabilize the eEF2-GDPribosome complex, we hypothesized that proteins in the stalk were candidate biochemical targets of sordarin.…”
Section: L10e Mutants and Eef2 Functionmentioning
confidence: 99%
“…The prokaryotic L7/L12 ribosomal proteins have been studied extensively by many physical and biological techniques, but much less is known about the structure and function of prokaryotic or eukaryotic L10. L10 is among the proteins reported to be cross-linked to eEF2 in 80S ribosomes by bifunctional reagents (13). In yeast, mutational analysis of the L10e ribosomal protein gene has shown that only L10e is essential, and that the carboxyl-terminal 132 amino acids of the L10e protein are required for viability.…”
mentioning
confidence: 99%
“…Ears were hand pollinated and harvested at 10,15,20,25,30, and 40 days postpollination (DPP) and after complete desiccation to isolate embryos (including the scutellum and embryonic axis), aleurone (tissue included the aleurone layer and attached pericarp), and endosperm (refers to tissue within the pericarp and aleurone, excluding the embryo).…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the level of P-proteins in yeast ribosomes is affected by the metabolic state of the cell and possibly reflects the translational activity of the ribosome. The presence of these proteins in ribosomes has been shown to stimulate the eEF2-dependent GTPase activity of ribosomes (13)(14)(15)(16)(17), poly(U)-directed phenylalanine synthesis (14,18), and eEF1A binding (19). Hence, modulation of the 12-kDa P-protein component of ribosomes may impart eukaryotes with a means of ribosomeregulated translational control.…”
mentioning
confidence: 99%